Personnel/human resource management - DeCenzo, david A.; Robbins, Stephen P. (New Delhi : Prentice-Hall of India, 1998)
Business
Keywords: Personnel management; Human resource management; Employment opportunity; Development; Motivation; Compensation; Industrial relation